Expression of Deiodinase Genes in Intraoperative Samples of Ligamentum FlavumLigamentum Flavum in Patients with Stenotic Processes of the Spinal Canal and Dural Sac on the Lumbar Spine - L. V. Rodionova; L. G. Samoilova; A. V. Nevezhina; I. A. Shurygina (Acta Biomedica Scientifica, 2019)
Background. Mechanisms are known that allow partial local regulation of the thyroid status of tissues using peripheral conversion of iodothyronines, which determines the local level of metabolic activity. The molecular mechanisms of degenerative-dystrophic changes in the ligamentum flavum are not well understood; only a few studies on the expression of genes in this substrate have been published.The aim of the study was to identify key factors in the peripheral conversion of iodothyronines in ligamentum flavum in patients with stenosis of spinal canal and dural sac in the lumbar spine and to evaluate the features of the expression of deiodinase genes depending on the severity of ossification processes of ligamentum flavum.Methods. A group of patients with stenotic processes of the spinal canal was examined: 31 people (15 men, 16 women). The average age was45.73 ± 1.95years. In intraoperatively collected samples of ligamentum flavum, the expression ofdeiodinase genes (real time PCR) was studied and the severity of ossification processes was evaluated using a histopathological study.Results. The key factors of peripheral conversion of iodothyronines in intraoperative bioptates of the ligamentum flavum of patients (n = 31) with stenosis of the spinal canal at the lumbar level were revealed. Information was obtained on the local level of metabolic activity in the focus of pathology. The intensity and variability of deiodinase gene expression in ligamentum flavum samples were evaluated. The distribution of deiodinase gene expression patterns in groups formed on the basis of presence/absence of ossification of ligamentum flavum was found. Various variants of peripheral conversion of iodothyronines in biopsy samples of the yellow ligament of the operated patients were determined and the frequency of their occurrence was estimated.Conclusion. The key factors ofperipheral conversion of iodothyronines in intraoperative biopsy samples of the ligamentum flavum of patients with degenerative diseases of the spine were revealed for the first time. The reasons for the differences in tissue metabolism of iodothyronines and the place in the pathogenesis of stenotic processes are yet to be found.